Effect of Bi2O3 content on properties of (Na 2O, K2O)-SiO2-CaO-Al2O 3-B2O3 glass system - P. Dararutana (2018)
(Na2O, K2O)-SiO2-CaO-Al2O 3-B2O3 glass system with 25-60 wt-% in concentration variations of Bi2O3 was fabricated in the laboratory scale using the conventional melting method. The values of refractive index, density and dielectric constant of the glass samples were measured at room temperature. It was found that the values of refractive index and density increased with increase in Bi2O3 content. The dielectric constant decreased with addition of Bi2O3 content up to 35 mol.-% and increased beyond this concentration. The colours of the glass samples changed from colourless to yellow when Bi2O3 concentration increased. The relationship between the properties such as, refractive index, density, dielectric constant and Bi2O3 content was also analysed and discussed. The results suggested that the bismuth bearing glass can be used as a suitable candidate to replace lead and/or barium based glasses. © W. S. Maney & Son Ltd. 2009.